Implementation Of The Tell-Show-Do Method In The Development Of Holistic Learning: Optimizing The Achievements Of 3 Learning Domains (Cognitive, Affective, Psychomotor) - Ida zuhroidah; Mokh. Sujarwadi; Mukhammad Toha; Dimas Hadi Prayoga (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Comprehensive competency, the integration of three learning domains (cognitive, affective, and psychomotor), is the primary target for graduates in nursing education. In reality, these three learning domains are often not achieved through conventional learning methods. The Tell-Show-Do method is expected to provide an effective solution for achieving holistic learning simultaneously. The purpose of this study is to analyze the effectiveness of the Tell-Show-Do method in optimizing holistic learning outcomes (cognitive, affective, and psychomotor). Methods: This quasi-experimental study, with a pre-test, post-test, and control group design, involved 122 D3 Nursing students from the Pasuruan City Campus, divided into two groups: treatment (n=61) and control (n=61). Data were analyzed using the Paired Sample T-Test, Independent Sample T-Test, and Mann-Whitney U test, with a significance level of α=0.05. Results: The TSD method showed convincing significance in all three domains: Cognitive (Δ=+7.77, p<0.001, d=2.76), Affective (Δ=+9.72, p<0.001, d=3.47), and Psychomotor (Δ=+10.26, p<0.001, d=3.80). The control group did not show any significant improvement (p>0.05). Conclusions: The Tell-Show-Do method has a significant impact on all three domains of learning outcomes, particularly psychomotor skills. Recommendation: Integrate TSD into the nursing education curriculum.